Paradoks Transparansi Semu (Hollow Transparency) pada E-Goverment Tingkat Mikro: Evaluasi Teknis Website Kecamatan Wilayah Kota Salatiga - Muhammad Yanwar Darmadi Putra; Hafids Haryonno; Augustin Rina Herawati (Universitas Tribhuwana Tunggadewi, 2025)
E-government evaluation in Indonesia often focuses on macro-level policies, leaving the technical readiness of micro-level institutions (districts) as the frontline of public service rarely audited objectively. This study aims to evaluate the technical performance of district websites in Salatiga City using an automated usability testing approach. Utilizing Google PageSpeed Insights, this study measures four key indicators: performance, accessibility, best practices, and SEO. The results reveal a paradox of